PENGARUH SUPERVISI KEPALA SEKOLAH DAN BUDAYA SEKOLAH TERHADAP EFEKTIVITAS SEKOLAH SDN SE KECAMATAN SUNGAI SEMBILAN KOTA DUMAI - Hernita; Isjoni; David Chairilsyah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
According to the author's observations, it is found the indicated phenomenon that public elementary school effectiveness is categorized as low in Sungai Sembilan, Dumai. The phenomena are that school achievement and goals have not been understood by all school members, the low creativity of the principal in implementing the school curriculum, the lack of school program development in order to build students’ character, and principals are less sensitive to the problems faced by teachers. The main purpose of the research described in this article is to analyze the effect of principal supervision and school culture on the effectiveness of public elementary schools in the Sungai Sembilan sub-district, Dumai. The type of research was quantitative research, and the research used a survey method by using a questionnaire as a data collection tool. The population of the research involved 112 people. The sampling technique was carried out by proportional random sampling in order to obtain the number of 87 people. The data analysis technique was carried out in two stages, descriptive and inferential statistics. In addition, the data obtained were analyzed by regression analysis, regression coefficient, and coefficient of determination. The results showed that there was a significant influence between the principal's supervision and school effectiveness, which was 40%. There was a significant influence between school culture and school effectiveness, which was 83%, and there was a mutual influence between principal supervision and school culture on school effectiveness, which was 83%. Thus, the influence of the principal's supervision variable and school culture on the effectiveness of the school was classified into high interpretation.